In vitro morphogenesis and acclimatization of Asparagus officinalis L. - Fatimah Mat Rasad (2019)
The purpose of this research was to examine morphogenesis of Asparagus officinalis L. through tissue culture system. The experimental design used in this study was Completely Randomized Design (CRD) and 30 samples were used in each treatment. Complete plant regeneration was successfully achieved when stem and root aseptic explants was cultured on MS medium supplemented with various combinations of plant growth regulators. MS medium supplemented with 2.0 mg/L BAP was found to be the optimum medium and stem explant was the most responsive explant producing 6.233 0.810 shoots per explant. MS medium supplemented with 1.5 mg/L NAA was most optimum for root induction with 10.567 0.841 roots per explant. Optimum callus induction was obtained when root explants were culture on MS medium fortified with 1.0 mg/L BAP and 1.0 mg/L NAA. Friable cream callus was produced. Meanwhile, the study with other auxin and cytokinin also showed the complete plant regeneration. MS medium supplemented with 0.5 mg/L BAP + 1.5 mg/L IAA was the best treatment and root explant was the most responsive for shoot regeneration with 10.200 1.011. MS medium supplemented with 0.5 mg/L Kinetin + 1.5 mg/L NAA was found to be the optimum treatment for root induction with 12.033 1.054. The best callus induction was obtained when stem explants were cultured on MS medium supplemented with 0.5 mg/L Kinetin + 1.5 mg/L NAA (2.319 0.035). For the production of synthetic seeds, Asparagus officinalis L. were produced when microshoots were encapsulated with 4.0% sodium alginate solution added with 1.5 mg/L BAP and 1.0 mg/L NAA. Synthetic seeds germination rate was 5.672 0.430 shoots per explant. Finally, acclimatization of Asparagus officinalis L. was accomplished when plantlets were transferred to the combination of black and red soil (2:1) with 93.33% survival rate. In conclusion, the main result showed that morphogenesis of Asparagus officinalis L. through tissue culture system was successfully achieved. The implication of this research is higher crop production could be obtained in agriculture industry especially in Malaysia.